2021
DOI: 10.14366/usg.20162
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound findings in peliosis hepatis

Abstract: Purpose: The aim of this study was to retrospectively evaluate contrast-enhanced ultrasound (CEUS) findings in patients with peliosis hepatis (PH).Methods: A retrospective analysis was conducted of CEUS features in 24 patients with histopathologically confirmed PH (11 men and 13 women; mean age, 32.4±7.1 years; range, 28 to 41 years). All lesions were histologically proven, either by core needle biopsy (n=10) or by hepatic surgery (n=14).Results: The mean size was 36.8±12.4 mm (range, 10 to 80 mm). On B-mode u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 29 publications
2
24
1
Order By: Relevance
“…In comparison to the results of the study by Dong et al., the lesion we present is in congruence with the described arterial hyperenhancement—but our case showed early progressive washout, whereas the authors concluded washout in the very late portal venous phase (after 1 minute) to be characteristic in peliosis hepatis [3] . Furthermore, 83.3% of the included lesions were described to be heterogeneously hypoechoic, whereas the case we present had hyperechoic appearance in B-mode US [3] .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In comparison to the results of the study by Dong et al., the lesion we present is in congruence with the described arterial hyperenhancement—but our case showed early progressive washout, whereas the authors concluded washout in the very late portal venous phase (after 1 minute) to be characteristic in peliosis hepatis [3] . Furthermore, 83.3% of the included lesions were described to be heterogeneously hypoechoic, whereas the case we present had hyperechoic appearance in B-mode US [3] .…”
Section: Discussionsupporting
confidence: 91%
“…Perfusion pattern of peliosis hepatis in CEUS are quite variable including a variety of B-mode findings with hyper-, iso- and hypoechogenicity [3 , 4] . While the solitary FLL showed no PET avidity, CEUS clearly identified suspicious contrast enhancement pattern in form of early, irregular arterial inflow without following a typical enhancement pattern known for haemangioma or focal nodular hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to current guidelines, the washout feature of CEUS is an important clue for distinguishing malignant from benign FLLs [ 11 , 25 ]. However, previous studies also showed that not all HCCs show washout during the late phase.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, conventional ultrasound (US) and CEUS features of less common FLL and vascular have been described in detail [6][7][8][9][10]. In this current paper series, we aim to summarize the US and CEUS features of very rare FLL where there are limited reports and figures published in order to create a library of these rare lesions [10][11][12][13][14][15][16][17][18][19]. Parasites and fungal diseases have manifestations in the liver that pose a diagnostic challenge.…”
Section: Introductionmentioning
confidence: 99%